"In-situ" lipase-catalyzed cotton coating with polyesters from ethylene glycol and glycerol. (March 2018) - Zhao, Xiaoman; Noro, Jennifer; Fu, Jiajia; Wang, Hongbo; Silva, Carla; Cavaco-Paulo, Artur
Graphical abstract: Highlights: Several polyesters were bio-synthesized from ethylene glycol, glycerol and di-esters. A conversion rate of 88.5% was achieved for bio-polymerization of poly (ethylene adipate). Oligomers mainly from dimmers to trimers were formed. The in situ bio-polymerization imparts hydrophobicity to cotton. Abstract: Several polyesters were synthesized from ethylene glycol, glycerol and adipate, succinate dimethyl esters. Immobilized Candida antarctica lipase B was used as catalyst for 6 h under vacuum at 70 °C without any further solvents. The highest conversion rate of 88.5% occurred for the polymerization of poly(ethylene adipate), evaluated by 1 H NMR. MALDI-TOF analysis indicated that most of the oligomers formed were dimers or trimers. After successfully synthesize the polyesters we set-up the optimal conditions for their in-situ coating onto cotton substrates with a soluble lipase from Thermomyces lanuginosus. This work presents a novel bio-approach to impart hydrophobic properties to coated cotton-based fibre materials.